Inovasi Pengembangan Kawasan Wisata Berkelanjutan di Objek Wisata Marimbunna Kelurahan Tikala - Defri Agung Sampe; Christian Sampetoding; Dirvan Stephen Ramba Bonga; Pebrianti Silitonga; Olivia Devi (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2022)
A tourist area is a valuable asset for a region, which not only provides sustainable economic potential, but also reflects and promotes its rich cultural, natural and historical heritage. Along with developments over time, changes in tourist behavior patterns, and demands for more memorable tourist experiences, developing tourist areas has become very important. The Marimbunna tourist attraction is a tourist destination that offers typical Toraja cultural heritage, especially in the form of burial or funeral tourism. The aim of this tourist area development innovation program is to create tourism destinations that are sustainable, competitive and attractive for tourists. The methods used in this service are field observation, interviews with the community, identifying problems and determining work objectives. The results of the work program activities include comparative studies, improvements to facilities and infrastructure, site cleaning, and outreach about the importance of preserving cultural tourism objects.